Long-term hyperglycaemia exerts contrasting effects on M1- and M2-like macrophages - Margaryan, Sona; Poghosyan, David; Ghonyan, Susanna; Hakobyan, Lina; Martirosyan, Anush; Manukyan, Gayane (Frontiers in Immunology, 2025)
IntroductionChronic hyperglycemia can contribute to metabolic disorders, disrupting cellular homeostasis and potentially leading to immunological disturbances. As highly adaptable innate immune cells, macrophages can effectively utilize glucose for energy and adjust their activities in response to environmental changes. We hypothesized that hyperglycemia induces distinct effects on M1 and M2 macrophages, thereby promoting their divergent roles in the inflammatory response.MethodsFor this, we applied an in vitro hyperglycemia model to investigate its impact on M1- and M2-like macrophages differentiated from primary monocytes.ResultsM1-like macrophages exhibited diminished capacity to produce reactive oxygen species (ROS), IL-6, TNF-α, as well as reduced antigen presentation and co-stimulatory abilities under long exposure to high glucose. In contrast, M2-like macrophages showed a shift toward M1 polarization, characterized by increased production of ROS and IL-6, upregulation of CD86 and HLA-DR expression, and reduced reparative abilities. We also observed disturbance of endotoxin tolerance evidenced by increased production of TNF-α and diminished phagocytic ability.DiscussionThe results suggest that hyperglycemia disrupts the typical functional dichotomy of M1 and M2 macrophages, which may explain mixed polarization of tissue macrophages in individuals with metabolic syndromes associated with chronic hyperglycemia.